Dinámica del crecimiento, sobrevivencia y calidad de una plantación de Cedrelinga cateniformis D. Ducke (fabaceae) en un área degradada del CIEFOR “Puerto Almendra”, Loreto. 2023 - Sevillano Montoya, Marcio Paolo (2023)
The study was conducted at the facilities of the Forestry Research and Teaching Center CIEFOR "Puerto Almendra" and the project "Provenance trials of forest and agricultural species of the Peruvian Amazon" attached to the National University of the Peruvian Amazon (UNAP) through the Faculty of Forestry Sciences, located in the district of San Juan Bautista, province of Maynas, Loreto region. The main objective was to know the dynamics of growth, survival and quality of a plantation of Cedrelinga cateniformis D. Ducke (Fabaceae) in a degraded area of CIEFOR "Puerto Almendra". The results report that the greatest increase in diameter was recorded in subplot 3, with a value of 2.79 cm increase at the end of the evaluation period. On the other hand, the greatest increase in height occurred in subplot 1, with a value of 104.58 cm increase at the end of the evaluation period. Likewise, there was a 73% survival rate of "tornillo" plants at the end of the evaluation period, while mortality reached 27% respectively. Finally, according to the coefficient of variation of the number of plants per hectare, the value of 13.66% indicates that the plantation has an acceptable quality.